High-stability anti-whitening nickel paste for MLCC (multilayer ceramic capacitor) and preparation method of high-stability anti-whitening nickel paste

By pretreating barium titanate powder with titanate coupling agent and combining with dispersant and organic carrier, the problem of floating color during standstill is solved, and high stability and anti-floating whitening is achieved. Nickel slurry of effect.

CN119418981APending Publication Date: 2025-02-11SHANGHAI JIANGJU NEW MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411445030.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Traditional nickel slurry is prone to precipitation and floating color problems during standstill, which affects its uniformity and stability, and thus affects the electrical performance and reliability of the capacitor.

Method used

The titanate coupling agent bis(dioctoxypyrophosphate)ethylene titanate is used as a powerful anti-whitening additive to pretreat the barium titanate powder and disperse it with a dispersant and an organic carrier. , homogenize the treatment to form a high stability and anti-floating nickel slurry.

Benefits of technology

The high stability and anti-whitening effect of nickel slurry are achieved. After being left for 180 days, there is no whitening or layering, and the appearance is clear, avoiding problems such as screen printing, sticking nets, white dots, and hypertrophy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119418981A_ABST
    Figure CN119418981A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nickel paste materials for MLCC, and discloses high-stability anti-whitening nickel paste for MLCC and a preparation method thereof, the nickel paste is prepared from the following raw materials by weight: 45-55 parts of nickel powder, 5-15 parts of barium titanate powder, 0.2-1.5 parts of a potent anti-whitening auxiliary agent, 0.2-2.5 parts of a dispersant, 30-40 parts of an organic carrier and 5-12 parts of medicinal terpilenol; wherein the particle size of the nickel powder is 100-400 nm, the particle size of the barium titanate powder is 50-100 nm, the powerful anti-whitening auxiliary agent is a titanate coupling agent, and the titanate coupling agent is bis (dioctyloxy pyrophosphate) ethylene titanate; the organic carrier is prepared from resin and a solvent in a mass ratio of (10-20%): (80-90%); wherein the barium titanate powder is pretreated by the following steps: firstly, treating the barium titanate powder by using the powerful anti-whitening auxiliary agent, and then adding a dispersing agent and organic resin for treatment; the nickel powder is pretreated by using the organic carrier and the dispersing agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nickel paste materials for MLCC, and specifically relates to a highly stable and anti-whitening nickel paste for MLCC and a preparation method thereof. Background Art

[0002] Multilayer ceramic capacitors (MLCCs) are important electronic components, mainly used in mobile phones, 5G communications, automotive electronics and other fields. With the rise of domestic high-end 5G mobile phones, MLCC products have greater development needs, and the domestic demand for MLCCs will increase in the future. Each high-end mobile phone requires 1500-1600 small-size MLCCs.

[0003] As an indispensable component in modern electronic devices, the performance of MLCC directly affects the stability and reliability of the entire product system. In the manufacturing process of MLCC, nickel paste is the key material for forming the inner electrode layer, and its quality is directly related to the final performance of the capacitor. However, in the static process, the traditional nickel paste often has the problem of precipitation and floating color of barium titanate ceramic powder (i.e. "floating white"), which not only affects the uniformity and stability of the nickel paste, but also may cause defects in the internal structure of the capacitor, thereby affecting its electrical performance and reliability. Although the traditional treatment method for improving dispersion can improve the dispersion of powder in nickel paste to a certain extent, on the one hand, the current existing literature uses coupling agents, dispersants or emulsification systems to improve the dispersion effect, but cannot guarantee storage stability. After standing or storing for a period of time, the stability decreases and the aforementioned floating white phenomenon will occur; on the other hand, the particle size of the powder currently used is getting smaller and smaller, and it becomes more difficult to achieve uniform dispersion and storage stability, and it is more likely to have problems of uneven dispersion and storage instability. There is currently no perfect solution to this problem. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a highly stable and anti-whitening nickel paste for MLCC, which has excellent dispersibility and storage stability, and can effectively reduce or eliminate the whitening phenomenon of nickel paste during long-term storage. The high stability means that the nickel paste has no whitening, no stratification, and a clear appearance when it is left standing for more than 180 days.

[0005] The technical solution of the present invention is as follows:

[0006] The invention discloses a highly stable and anti-whitening nickel paste for MLCC, which is prepared from the following raw materials in parts by weight: 45-55 parts of nickel powder, 5-15 parts of barium titanate powder, 0.2-1.5 parts of a strong anti-whitening aid, 0.2-2.5 parts of a dispersant, 30-40 parts of an organic carrier, and 5-12 parts of medicinal pinene alcohol;

[0007] The particle size of the nickel powder is 100-400 nm, the particle size of the barium titanate powder is 50-100 nm, the strong anti-whitening agent is a titanate coupling agent, and the titanate coupling agent is bis(dioctyloxypyrophosphate)ethylene titanate; the organic carrier is made of a resin and a solvent in a mass ratio of 10-20%:80-90%, wherein the barium titanate powder is pretreated as follows: first treated with the strong anti-whitening agent, and then treated with a dispersant and an organic resin; the nickel powder is pretreated with the organic carrier and the dispersant.

[0008] The present invention selects the above-mentioned strong anti-whitening aid, dispersant and other components and sets the pretreatment, so that the titanate coupling agent is combined with the surface of the barium titanate powder and the organic resin at both ends through chemical reaction, wherein the present invention selects the titanate coupling agent as a strong anti-whitening aid, and can obtain a highly stable and anti-whitening nickel paste for MLCC, while the use of other types of conventional coupling agents cannot obtain the high stability and anti-whitening performance. In particular, the titanate coupling agent of the present invention is bis (dioctyloxy pyrophosphate) ethylene titanate. The nickel paste prepared by the titanate coupling agent has been verified to have high stability and anti-whitening effects, and there is no whitening and no stratification when standing for more than 180 days, and the appearance is clear. Other titanate coupling agents do not have this effect.

[0009] In one embodiment of the present invention, preferably, the bis(dioctyloxypyrophosphate)ethylene titanate is a titanate coupling agent PN-311 purchased from Nanjing Pinning Coupling Agent Co., Ltd. This product is used in some embodiments of the present invention, but the present invention is not limited thereto. Similar products produced by other manufacturers, as long as they have the same purity specifications, can be used in the present invention and achieve similar effects.

[0010] In one embodiment of the present invention, preferably, the dispersant is a high molecular weight block copolymer containing pigment affinity groups.

[0011] In one embodiment of the present invention, preferably, the high molecular weight block copolymer containing pigment affinity groups is purchased from BYK-2163 of BYK Additives (Shanghai) Co., Ltd. The specific reagent defined herein is a product used in some embodiments of the present invention, which has been verified to have a good dispersion effect. The nickel slurry prepared using the dispersant has been verified to have high stability and anti-whitening effects, and has no whitening and stratification when left to stand for more than 180 days, and has a clear appearance. However, the present invention is not limited thereto, and high molecular weight block copolymers containing pigment affinity groups of similar structures or other types can be used in the present invention and achieve similar effects.

[0012] In one embodiment of the present invention, preferably, the solvent is medicinal pinene alcohol and solvent oil D80. In some embodiments, the medicinal pinene alcohol is purchased from Xilong Science Co., Ltd., and the solvent oil D80 is purchased from Royal Dutch Shell Petroleum Company.

[0013] In one embodiment of the present invention, preferably, the mass ratio of the medicinal pinene alcohol to the solvent oil D80 is 2 to 5: 1. Within this ratio range, the solvent dissolves the resin and has a better printing effect.

[0014] In one embodiment of the present invention, preferably, the resin is ethyl cellulose and polyvinyl acetal resin. The inventor has verified through experiments that the use of this resin combination can further improve the effect of high stability and anti-whitening. In some embodiments, ethyl cellulose is purchased from Dow Chemical Company and polyvinyl acetal resin is purchased from Sekisui Chemical Co., Ltd.

[0015] In one embodiment of the present invention, preferably, the mass ratio of the ethyl cellulose to the polyvinyl acetal resin is 1:0.2-0.4.

[0016] The present invention also discloses a method for preparing the above-mentioned highly stable and anti-whitening nickel paste for MLCC, comprising the following steps:

[0017] (1) Pretreatment of barium titanate powder: firstly disperse 5 to 15 parts of barium titanate powder, 0.2 to 1.5 parts of strong anti-whitening agent and 3 to 5 parts of medicinal pine alcohol, then add 0.1 to 1.0 parts of dispersant and 5 to 8 parts of organic carrier, and then disperse and homogenize to obtain barium titanate dispersion;

[0018] (2) Preparation of nickel slurry: First, 45-55 parts of nickel powder, 0.1-1.5 parts of dispersant, 10-15 parts of organic carrier and 1-6 parts of medicinal pine oil are dispersed and homogenized, and the obtained nickel powder dispersion is mixed with the barium titanate dispersion and 12-17 parts of organic carrier, and then dispersed and rolled, and the viscosity is adjusted with 1-2 parts of medicinal pine oil, and the nickel slurry is obtained by filtering.

[0019] In the above preparation method of the present invention, the step numbers (1) and (2) are only used for distinction and do not represent a particular order. Based on the above disclosure, a person skilled in the art can easily conceive that there is no order of precedence for the pretreatment of barium titanate powder and the treatment of nickel powder (first dispersing and homogenizing 45 to 55 parts of nickel powder, 0.1 to 1.5 parts of dispersant, 10 to 15 parts of organic carrier and 1 to 6 parts of medicinal pine alcohol). The pretreatment of barium titanate powder can be performed first and the treatment of nickel powder can be performed later, or the treatment of nickel powder can be performed first and the pretreatment of barium titanate powder can be performed later, or both can be performed simultaneously. It is only necessary that the pretreatment of barium titanate powder and the treatment of nickel powder be performed before the subsequent treatment step (mixing the obtained nickel powder dispersion with the barium titanate dispersion and 12 to 17 parts of organic carrier).

[0020] The above preparation method includes first pre-treating the barium titanate powder, the pre-treatment includes first using a strong anti-whitening aid to disperse the barium titanate powder in medicinal pine alcohol, and then adding a dispersant and an organic carrier containing a resin for treatment. The above preparation method also includes pre-treating the nickel powder, using a dispersant and an organic carrier to pre-treat the nickel powder in the presence of medicinal pine alcohol, then mixing the barium titanate dispersion obtained by the pre-treatment and adding an appropriate amount of organic carrier, and obtaining a nickel slurry through subsequent treatment. In addition, in the present invention, the medicinal pine alcohol, the dispersant, and the organic carrier are added in appropriate amounts in different steps, rather than all added in one processing step at one time. The above characteristics of the preparation method of the present invention better guarantee the dispersibility and stability of the nickel slurry product finally obtained.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The invention discloses a highly stable and white-resistant nickel paste for MLCC. The titanate coupling agent bis(dioctyloxypyrophosphate)ethylene titanate is used as a strong white-resistant additive to pretreat barium titanate powder. A dispersant and an organic carrier containing a resin are then used to disperse and homogenize the nickel powder. The dispersant and an organic carrier containing a resin are also used to pretreat the nickel powder. The dispersant stably disperses the nickel powder and the barium titanate powder in the slurry system through wetting and dispersion, steric hindrance effect and electrostatic stabilization. The titanate coupling agent reacts chemically to bond the two ends of the nickel powder to the surface of the barium titanate powder and the organic carrier. The resin is combined to form a molecular bridge-like effect, which helps the powder to be better dispersed in the slurry system, thereby improving the fluidity, dispersibility and storage stability of the slurry. The above treatment of the present invention can effectively prevent the barium titanate powder and the nickel powder from agglomerating and precipitating at the bottom of the slurry. At the same time, the preparation method of the present invention also optimizes the preparation process, and enables the nickel powder and the barium titanate powder to be more stably dispersed in the organic carrier, has excellent dispersion stability, and can effectively reduce or eliminate the whitening phenomenon of the nickel slurry. After standing for more than 180 days, the nickel slurry has no whitening, no stratification, a clear appearance, and no screen printing, sticking, white spots, hypertrophy and other problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is an appearance effect diagram of the nickel paste of Example 1 of the present invention after being left to stand for 30 days;

[0024] Figure 2 This is an appearance effect diagram of the nickel paste of Example 2 of the present invention after being left to stand for 30 days;

[0025] Figure 3 This is an appearance effect diagram of the nickel paste of Example 3 of the present invention after being left to stand for 30 days;

[0026] Figure 4 This is an appearance effect diagram of the nickel paste of Example 4 of the present invention after being left to stand for 30 days;

[0027] Figure 5 This is an appearance effect diagram of the nickel slurry of Comparative Example 1 of the present invention after being left to stand for 30 days;

[0028] Figure 6 This is an appearance effect diagram of the nickel slurry of Comparative Example 2 of the present invention after being left to stand for 30 days;

[0029] Figure 7 This is an appearance effect diagram of the nickel slurry of Comparative Example 3 of the present invention after being left to stand for 30 days;

[0030] Figure 8 This is an appearance effect diagram of the nickel slurry of Comparative Example 4 of the present invention after being left to stand for 30 days;

[0031] Fig. 9 Photos of the printed appearance of Examples 1-4 of the present invention and Comparative Examples 1-4. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0033] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0034] The present invention provides a highly stable and anti-whitening nickel paste for MLCC, which is prepared from the following raw materials in parts by weight: 45-55 parts of nickel powder, 5-15 parts of barium titanate powder, 0.2-1.5 parts of a strong anti-whitening aid, 0.2-2.5 parts of a dispersant, 30-40 parts of an organic carrier, and 5-12 parts of medicinal pine alcohol;

[0035] The particle size of the nickel powder is 100-400 nm, the particle size of the barium titanate powder is 50-100 nm, the strong anti-whitening agent is a titanate coupling agent, and the titanate coupling agent is bis(dioctyloxypyrophosphate)ethylene titanate; the organic carrier is made of a resin and a solvent in a mass ratio of 10-20%:80-90%; the barium titanate powder is pretreated as follows: first treated with the strong anti-whitening agent, and then treated with a dispersant and an organic resin; the nickel powder is pretreated with the organic carrier and the dispersant.

[0036] The nickel paste of the present invention has excellent fluidity and stability, can effectively reduce or eliminate the whitening phenomenon of the nickel paste, and the nickel paste has no whitening and stratification after being left to stand for more than 180 days, has a clear appearance, and has no screen printing, sticking, white spots, hypertrophy and other problems.

[0037] The reagents used in the following examples and comparative examples are as follows:

[0038] The titanate coupling agent is the titanate coupling agent PN-311 produced by Nanjing Pinning Coupling Agent Co., Ltd.

[0039] The dispersant is BYK-2163 produced by BYK Additives (Shanghai) Co., Ltd.

[0040] The medicinal pinene alcohol is purchased from Xilong Science Co., Ltd., and the solvent oil D80 is purchased from Royal Dutch Shell Petroleum Company.

[0041] The ethyl cellulose was purchased from Dow Chemical Company, and the polyvinyl acetal resin was purchased from Sekisui Chemical Co., Ltd.

[0042] The relevant process involved in the following examples and comparative examples is as follows:

[0043] 1. Pretreatment of barium titanate powder:

[0044] 1. First, use a high-speed disperser to disperse barium titanate powder, medicinal pine alcohol, and strong anti-whitening agent PN-311 for 1 hour;

[0045] 2. Add dispersant BYK-2163 and organic carrier (ethyl cellulose: printing modified PVB: medicinal pinene alcohol: solvent oil D80 = 10:3:62:25) to 1, and disperse in a high-speed disperser for 0.5h;

[0046] 3. Homogenization: The materials in 2 are homogenized by a high-pressure nano-homogenizer at a pressure of 25,000 psi to obtain a barium titanate dispersion.

[0047] 2. Nickel paste production:

[0048] 1. First, put nickel powder, medicinal pinene alcohol, dispersant BYK-2163 and organic carrier into Nano grinding machine for grinding and dispersion for 0.5h;

[0049] 2. The material in 1 is passed through a high pressure nano homogenizer and homogenized at a pressure of 15000 psi;

[0050] 3. Add the barium titanate dispersion prepared above and the remaining organic carrier (ethyl cellulose: printing modified PVB: medicinal pinene alcohol: solvent oil D80 = 10:3:62:25) to 2, and grind and disperse using a Nano grinder for 1 hour;

[0051] 4. The slurries 3 are rolled 3 to 5 times using a Swiss Buhler three-roll mill, adjusted to a suitable viscosity using medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry.

[0052] Example 1

[0053] A method for preparing a highly stable and anti-whitening nickel paste for MLCC according to embodiment 1 of the present invention comprises the following steps:

[0054] The raw materials were prepared according to the following weight proportions: 48 parts of 400nm nickel powder, 8 parts of 100nm barium titanate powder, 1 part of PN-311 strong anti-whitening agent, 31 parts of dispersant BYK-216, 32 parts of organic carrier (the ratio is ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25), and 10 parts of medicinal pine alcohol were used in addition to the organic carrier;

[0055] (1) 8 parts of 100 nm barium titanate powder, 3 parts of medicinal pine alcohol, and 1 part of strong anti-whitening agent PN-311 were put into a high-speed disperser for dispersion for 1 hour;

[0056] (2) Add 0.2 parts of dispersant BYK-2163 and 6.4 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) to (1), and disperse in a high-speed disperser for 0.5 h;

[0057] (3) passing the material in (2) through a high pressure nano homogenizer at a pressure of 25000 psi to obtain a barium titanate dispersion;

[0058] (4) 48 parts of 400 nm nickel powder, 5 parts of medicinal pine alcohol, 0.8 parts of dispersant BYK-2163 and 12 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) were put into a Nano mill and ground and dispersed for 0.5 h;

[0059] (5) putting the material in (4) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15000 psi;

[0060] (6) The material in (5) was mixed with the barium titanate dispersion prepared in (3), and 13.6 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) was added, and the mixture was ground and dispersed using a Nano grinder for 1 hour;

[0061] (7) The slurry in (6) was rolled three times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 2 parts of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the slurry were tracked. After being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, the appearance of the slurry was as follows. Figure 1 The other appearance results are shown in Table 1.

[0062] Example 2

[0063] A method for preparing a highly stable and anti-whitening nickel paste for MLCC according to embodiment 1 of the present invention comprises the following steps:

[0064] Prepare the following raw materials in parts by weight: 46 parts of 180nm nickel powder, 10 parts of 50nm barium titanate powder, 1 part of PN-311 strong anti-whitening agent, 1 part of BYK-2163 dispersant, 30 parts of organic carrier (ratio of ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25), and 12 parts of medicinal pine alcohol in addition to the organic carrier;

[0065] (1) Put 10 parts of 50nm barium titanate powder, 5 parts of medicinal pine alcohol, and 1 part of strong anti-whitening agent PN-311 into a high-speed disperser for dispersion for 1 hour;

[0066] (2) Add 0.2 parts of dispersant BYK-2163 and 6.4 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) to (1), and disperse in a high-speed disperser for 0.5 h;

[0067] (3) The material in (2) was homogenized by a high-pressure nano-homogenizer at a pressure of 25,000 psi to obtain a barium titanate dispersion.

[0068] (4) 46 parts of 180 nm nickel powder, 5 parts of medicinal pine alcohol, 0.8 parts of dispersant BYK-2163 and 12 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) were put into a Nano mill and ground and dispersed for 0.5 h;

[0069] (5) putting the material in (4) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15000 psi;

[0070] (6) The material in (5) was mixed with the barium titanate dispersion prepared in (3), and 13.6 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) was added, and the mixture was ground and dispersed using a Nano grinder for 1 hour;

[0071] (7) The slurry in (6) was rolled 5 times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 2 parts of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the slurry were tracked. After being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, the appearance of the slurry was as follows. Figure 2 The other appearance results are shown in Table 1.

[0072] Example 3

[0073] A method for preparing a highly stable and anti-whitening nickel paste for MLCC according to embodiment 3 of the present invention comprises the following steps:

[0074] Prepare the following raw materials in parts by weight: 45 parts of 300nm nickel powder, 9 parts of 100nm barium titanate powder, 0.2 parts of PN-311 strong anti-whitening agent, 0.3 parts of dispersant BYK-2163, 40 parts of organic carrier (ratio of ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 15:5:65:15), and 5.5 parts of medicinal pine alcohol in addition to the organic carrier;

[0075] (1) 9 parts of 100 nm barium titanate powder, 3 parts of medicinal pine alcohol, and 0.2 parts of strong anti-whitening agent PN-311 were put into a high-speed disperser for dispersion for 1 hour;

[0076] (2) Add 0.1 parts of dispersant BYK-2163 and 8 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 15:5:65:15) to (1), and disperse in a high-speed disperser for 0.5 h;

[0077] (3) passing the material in (2) through a high pressure nano homogenizer at a pressure of 25000 psi to obtain a barium titanate dispersion;

[0078] (4) 45 parts of 300 nm nickel powder, 1.5 parts of medicinal pine alcohol, 0.2 parts of dispersant BYK-2163 and 15 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 15:5:65:15) were put into a Nano mill and ground and dispersed for 0.5 h;

[0079] (5) putting the material in (4) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15000 psi;

[0080] (6) The material in (5) was mixed with the barium titanate dispersion prepared in (3), and 17 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 15:5:65:15) was added, and the mixture was ground and dispersed using a Nano grinder for 1 hour;

[0081] (7) The slurry in (6) was rolled 4 times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 1 part of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the slurry were tracked. After being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, the appearance of the slurry was as follows. Figure 3 The other appearance results are shown in Table 1.

[0082] Example 4

[0083] A method for preparing a highly stable and anti-whitening nickel paste for MLCC according to Example 4 of the present invention comprises the following steps:

[0084] The raw materials were prepared according to the following weight proportions: 45 parts of 200nm nickel powder, 9 parts of 100nm barium titanate powder, 1.5 parts of PN-311 strong anti-whitening agent, 32 parts of dispersant BYK-216, 37 parts of organic carrier (the ratio is ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 15:5:65:15), and 5.5 parts of medicinal pine alcohol were used in addition to the organic carrier;

[0085] (1) 9 parts of 100 nm barium titanate powder, 3 parts of medicinal pine alcohol, and 1.5 parts of strong anti-whitening agent PN-311 were put into a high-speed disperser for dispersion for 1 hour;

[0086] (2) Add 0.5 parts of dispersant BYK-2163 and 8 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 15:5:65:15) to (1), and disperse in a high-speed disperser for 0.5 h;

[0087] (3) passing the material in (2) through a high pressure nano homogenizer at a pressure of 25000 psi to obtain a barium titanate dispersion;

[0088] (4) 45 parts of 200 nm nickel powder, 1.5 parts of medicinal pine alcohol, 1.5 parts of dispersant BYK-2163 and 15 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 15:5:65:15) were put into a Nano mill and ground and dispersed for 0.5 h;

[0089] (5) putting the material in (4) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15000 psi;

[0090] (6) The material in (5) was mixed with the barium titanate dispersion prepared in (3), and 14 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pinene alcohol: solvent oil D80 = 15:5:65:15) was added, and the mixture was ground and dispersed using a Nano grinder for 1 hour;

[0091] (7) The slurry in (6) was rolled three times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 1 part of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the slurry were tracked. After being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, the appearance of the slurry was as follows. Figure 4 The other appearance results are shown in Table 1.

[0092] Comparative Example 1

[0093] A method for preparing a nickel paste for MLCC according to Comparative Example 1 of the present invention comprises the following steps:

[0094] The raw materials were prepared according to the following weight proportions: 48 parts of 400nm nickel powder, 8 parts of 100nm barium titanate powder, 1 part of BYK-2163 dispersant, 32 parts of organic carrier (ratio: ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25), and 11 parts of medicinal pine alcohol were used in addition to the organic carrier. The difference from Example 1 is that the strong anti-whitening agent PN-311 is not added.

[0095] (1) 8 parts of 100 nm barium titanate powder and 4 parts of medicinal pinene alcohol were put into a high-speed disperser for dispersion for 1 hour;

[0096] (2) Add 0.2 parts of dispersant BYK-2163 and 6.4 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) to (1), and disperse in a high-speed disperser for 0.5 h;

[0097] (3) The material in (2) was homogenized by a high-pressure nano-homogenizer at a pressure of 25,000 psi to obtain a barium titanate dispersion.

[0098] (4) 48 parts of 400 nm nickel powder, 5 parts of medicinal pine alcohol, 0.8 parts of dispersant BYK-2163 and 12 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) were put into a Nano mill and ground and dispersed for 0.5 h;

[0099] (5) putting the material in (4) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15000 psi;

[0100] (6) The material in (5) was mixed with the barium titanate dispersion prepared in (3), and 13.6 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) was added, and the mixture was ground and dispersed using a Nano grinder for 1 hour;

[0101] (7) The slurry in (6) was rolled three times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 2 parts of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the slurry were tracked. After being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, the appearance of the slurry was as follows. Figure 5 The remaining appearance results are shown in Table 1.

[0102] Comparative Example 2

[0103] A method for preparing a nickel paste for MLCC according to Comparative Example 2 of the present invention comprises the following steps:

[0104] The following raw materials were prepared in parts by weight: 48 parts of 400nm nickel powder, 8 parts of 100nm barium titanate powder, 1 part of PN-311 strong anti-whitening agent, 32 parts of organic carrier (ratio: ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25), and 11 parts of medicinal pine alcohol were used in addition to the organic carrier. The difference from Example 1 is that the dispersant BYK-2163 is not added;

[0105] (1) 8 parts of 100 nm barium titanate powder, 1 part of strong anti-whitening agent PN-311, and 3 parts of medicinal pinene alcohol were put into a high-speed disperser for dispersion for 1 hour;

[0106] (2) Add 6.4 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) to (1) and disperse in a high-speed disperser for 0.5 h;

[0107] (3) The material in (2) was homogenized by a high-pressure nano-homogenizer at a pressure of 25,000 psi to obtain a barium titanate dispersion.

[0108] (4) 48 parts of 400 nm nickel powder, 6 parts of medicinal pine alcohol, and 12 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) were put into a Nano mill and ground and dispersed for 0.5 h;

[0109] (5) putting the material in (4) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15000 psi;

[0110] (6) The material in (5) was mixed with the barium titanate dispersion prepared in (3), and 13.6 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) was added, and the mixture was ground and dispersed using a Nano grinder for 1 hour;

[0111] (7) The slurry in (6) was rolled three times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 2 parts of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the slurry were tracked. After being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, the appearance of the slurry was as follows. Figure 6 The remaining appearance results are shown in Table 1.

[0112] Comparative Example 3

[0113] A method for preparing nickel paste for MLCC according to Comparative Example 3 of the present invention comprises the following steps:

[0114] The following raw materials were prepared in parts by weight: 48 parts of 400nm nickel powder, 8 parts of 100nm barium titanate powder, 1 part of PN-311 strong anti-whitening agent, 1 part of BYK-2163 dispersant, 32 parts of organic carrier (ratio: ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25), and 10 parts of medicinal pine alcohol were used in addition to the organic carrier. The difference from Example 1 is that the nickel powder and barium titanate are not treated with the special process to form a dispersion;

[0115] (1) 8 parts of 100nm barium titanate powder, 48 parts of 400nm nickel powder, 1 part of strong anti-whitening agent PN-311, 1 part of BYK-2163 dispersant, 32 parts of organic carrier, and 8 parts of medicinal pinene alcohol were put into a high-speed disperser for dispersion treatment for 1 hour;

[0116] (2) placing the material in (1) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15,000 psi;

[0117] (3) The material in (2) was rolled three times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 2 parts of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the static state were tracked. Among them, the appearance of the nickel slurry after being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60% was as follows. Figure 7 As shown in the figure, serious whitening occurs. The other appearance results are shown in Table 1.

[0118] Comparative Example 4

[0119] A method for preparing a nickel paste for MLCC according to Comparative Example 4 of the present invention comprises the following steps:

[0120] The raw materials were prepared according to the following weight proportions: 48 parts of 400nm nickel powder, 8 parts of 100nm barium titanate powder, 1 part of KR-TTS Ajinomoto Co., Ltd. (refer to the titanate coupling agent used in Japanese patent JP4012795B2), 31 parts of dispersant BYK-216, 32 parts of organic carrier (ratio of ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25), and 10 parts of medicinal pine alcohol were used in addition to the organic carrier;

[0121] (1) 8 parts of 100 nm barium titanate powder, 3 parts of medicinal pine alcohol, and 1 part of KR-TTS Ajinomoto titanate coupling agent were put into a high-speed disperser for dispersion for 1 hour;

[0122] (2) Add 0.2 parts of dispersant BYK-2163 and 6.4 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) to (1), and disperse in a high-speed disperser for 0.5 h;

[0123] (3) passing the material in (2) through a high pressure nano homogenizer at a pressure of 25000 psi to obtain a barium titanate dispersion;

[0124] (4) 48 parts of 400 nm nickel powder, 5 parts of medicinal pine alcohol, 0.8 parts of dispersant BYK-2163 and 12 parts of organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) were put into a Nano mill and ground and dispersed for 0.5 h;

[0125] (5) putting the material in (4) into a high-pressure nano homogenizer and homogenizing it at a pressure of 15000 psi;

[0126] (6) The material in (5) was mixed with the barium titanate dispersion prepared in (3), and 13.6 parts of an organic carrier (ethyl cellulose: printing modified PVB: medicinal pine alcohol: solvent oil D80 = 10:3:62:25) was added, and the mixture was ground and dispersed using a Nano grinder for 1 hour;

[0127] (7) The slurry in (6) was rolled three times using a Swiss Buhler three-roll mill, and adjusted to a suitable viscosity using about 2 parts of medicinal pine oil, and filtered through a precision filter element to obtain a nickel inner electrode slurry. The nickel slurry was placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, and the appearance results of the long-term stability of the slurry were tracked. After being placed in an environment with a temperature of 20 to 30°C and a humidity of 30% to 60%, the appearance of the slurry was as follows. Figure 8 The other appearance results are shown in Table 1.

[0128] Test results:

[0129] The nickel pastes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were respectively canned and placed in an environment with a temperature of 20 to 30° C. and a humidity of 30% to 60%, and the appearance results were tracked. The specific test results are shown in Table 1 below.

[0130] Table 1

[0131] Leave to stand for 7 days Leave to stand for 30 days 90 days of static 180 days of static Example 1 No white floating, no stratification No white floating, no stratification No white floating, no stratification No white floating, no stratification Example 2 No white floating, no stratification No white floating, no stratification No white floating, no stratification No white floating, no stratification Example 3 No white floating, no stratification No white floating, no stratification No white floating, no stratification No white floating, no stratification Example 4 No white floating, no stratification No white floating, no stratification No white floating, no stratification No white floating, no stratification Comparative Example 1 Slightly whitened, layered Slightly whitened, layered Severe whitening and delamination Severe whitening and delamination Comparative Example 2 Slightly whitened, layered Slightly whitened, layered Severe whitening and delamination Severe whitening and delamination Comparative Example 3 Slightly whitened, layered Severe whitening and delamination Severe whitening and delamination Severe whitening and delamination Comparative Example 4 Slightly whitened, layered Severe whitening and delamination Severe whitening and delamination Severe whitening and delamination

[0132] From the results in Table 1,

[0133] Examples 1 to 4 had no whitening or stratification during standing for up to 180 days;

[0134] Comparative Example 1, which did not use the titanate coupling agent PN-311 as a strong anti-whitening agent, showed slight whitening and stratification after standing for 7 days, and severe whitening and stratification after standing for 90 days;

[0135] Comparative Example 2, which did not use the dispersant BYK-2163, showed slight whitening and stratification after standing for 7 days, and severe whitening and stratification after standing for 90 days;

[0136] Comparative Example 3 in which the nickel powder and barium titanate were not subjected to the pretreatment step showed slight whitening and stratification after standing for 7 days, and showed severe whitening and stratification after standing for 30 days.

[0137] Comparative Example 4 uses KR-TTS Ajinomoto Co., Ltd. titanate coupling agent (reference Japanese patent JP4012795B2) instead of the strong anti-whitening agent PN-311, but fails to achieve the effect of improving whitening. Slight whitening and stratification occur after standing for 7 days, and severe whitening and stratification occur after standing for 30 days.

[0138] The surface roughness of the nickel pastes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 after printing is shown in Table 2 below, and the printed appearance comparison results are shown in Fig. 9 .

[0139] Table 2

[0140]

[0141] From Table 2 above, the printed graphics of Examples 1 to 4 and Comparative Examples 1 to 4 are all clear, without problems such as screen printing, sticking, and white spots.

[0142] From the appearance of the photos in Table 2: Example 1 ≈ Example 2 ≈ Example 3 ≈ Example 4 > Comparative Example 2 > Comparative Example 4 > Comparative Example 1 > Comparative Example 3;

[0143] In terms of roughness, Example 2>Example 4>Example 3>Example 1>Comparative Example 1>Comparative Example 4>Comparative Example 2>Comparative Example 3.

[0144] The printing appearance and roughness results in Table 2 also prove that the nickel pastes of Examples 1-4 have good printing leveling performance without adding additional leveling agents after being treated with a strong anti-whitening agent, a dispersant and a special process.

[0145] In summary, the nickel inner electrode slurry prepared by the present invention uses a strong anti-whitening agent to pretreat the barium titanate powder, and in the presence of a dispersant, the strong anti-whitening agent is chemically reacted with the organic resin, and the nickel powder is pretreated with an organic carrier and a dispersant, and then the two are mixed to prepare the nickel inner electrode slurry, thereby achieving excellent stability during storage and use, and can effectively avoid the whitening phenomenon of the nickel paste; in addition, the nickel paste of the present invention also performs well in terms of printing appearance and surface roughness, and can be well applied to MLCC production.

[0146] Therefore, the MLCC nickel inner electrode slurry provided by the present invention can effectively solve the common nickel slurry whitening problem in the prior art, and has excellent storage and use stability. This slurry can be widely used in the preparation of BME (Base Metal Electrode) MLCC inner electrodes, and has important practical application value in the field of electronic components.

[0147] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A highly stable and anti-whitening nickel paste for MLCC, characterized in that: The invention is prepared from the following raw materials in parts by weight: 45-55 parts of nickel powder, 5-15 parts of barium titanate powder, 0.2-1.5 parts of a strong anti-whitening agent, 0.2-2.5 parts of a dispersant, 30-40 parts of an organic carrier and 5-12 parts of medicinal pinene alcohol; The particle size of the nickel powder is 100-400 nm, the particle size of the barium titanate powder is 50-100 nm; the strong anti-whitening agent is a titanate coupling agent, and the titanate coupling agent is bis(dioctyloxypyrophosphate)ethylene titanate; the organic carrier is made of a resin and a solvent in a mass ratio of 10-20%:80-90%; The barium titanate powder is pretreated as follows: firstly treated with the strong anti-whitening agent, and then treated with a dispersant and an organic resin; The nickel powder is pretreated with the organic carrier and the dispersant.

2. The highly stable and anti-whitening nickel paste for MLCC according to claim 1, characterized in that: The bis(dioctyloxypyrophosphate)ethylene titanate is a titanate coupling agent PN-311 purchased from Nanjing Pinning Coupling Agent Co., Ltd.

3. The highly stable and anti-whitening nickel paste for MLCC according to claim 1, characterized in that: The dispersant is a high molecular weight block copolymer containing pigment affinity groups.

4. The highly stable and anti-whitening nickel paste for MLCC according to claim 3, characterized in that: The dispersant is BYK-2163, a high molecular weight block copolymer containing pigment affinity groups, purchased from BYK Additives (Shanghai) Co., Ltd.

5. The highly stable and anti-whitening nickel paste for MLCC according to claim 1, characterized in that: The solvents are medicinal pinene alcohol and solvent oil D80.

6. The highly stable and anti-blushing nickel paste for MLCC according to claim 5, characterized in that: The mass ratio of the medicinal pinene alcohol to the solvent oil D80 is 2-5:

1.

7. The highly stable and anti-blushing nickel paste for MLCC according to claim 1, characterized in that: The resins are ethyl cellulose and polyvinyl acetal resin.

8. The highly stable and anti-blushing nickel paste for MLCC according to claim 7, characterized in that: The mass ratio of the ethyl cellulose to the polyvinyl acetal resin is 1:0.2-0.

4.

9. A method for preparing a highly stable and anti-blushing nickel paste for MLCC according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Pretreatment of barium titanate powder: firstly disperse 5 to 15 parts of barium titanate powder, 0.2 to 1.5 parts of strong anti-whitening agent and 3 to 5 parts of medicinal pine alcohol, then add 0.1 to 1.0 parts of dispersant and 5 to 8 parts of organic carrier, and then disperse and homogenize to obtain barium titanate dispersion; (2) Preparation of nickel slurry: First, 45-55 parts of nickel powder, 0.1-1.5 parts of dispersant, 10-15 parts of organic carrier and 1-6 parts of medicinal pine oil are dispersed and homogenized, and the obtained nickel powder dispersion is mixed with the barium titanate dispersion and 12-17 parts of organic carrier, and then dispersed and rolled, and the viscosity is adjusted with 1-2 parts of medicinal pine oil, and the nickel slurry is obtained by filtering.

Citation Information

Patent Citations

  • conductive paste

    JP4012795B2